Bioactivity of Six Plant Extracts on Adults of Demotispa neivai (Coleoptera: Chrysomelidae). Issue 1 (5th April 2015) - Martínez, Luis C.; Plata-Rueda, Angelica; Zanuncio, José C.; Serrão, José E.
Abstract : Demotispa neivai Bondar (Coleoptera: Chrysomelidae) damage oil palm fruits, which makes it necessary to develop products to control this insect. The mortality, repellency, and antifeeding effects on adults of D. neivai of six plant extracts of Azadirachta indica A. Juss. (Sapindales: Meliaceae), Ricinus communis (L.) (Malpighiaes: Euphorbiaceae), Citrus sinensis Oesbek (Sapindales: Rutaceae), Nicotiana tabacum (L.) (Slanales: Solanaceae), Capsicum annuum (L.) (Solanales: Solanaceae), and Artemisia absinthium (L.) (Asterales: Asteraceae) were determined: 1) the lethal concentration LC50-90, lethal time of D. neivai was evaluated after spraying the fruits of oil palm; 2) repellent effects of each ingredient were evaluated by calculating the index of repellency; 3) antifeeding effects with the rate of inhibition calculated between doses of 20 and 24 g/liter. The mortality of D. neivai was higher with the extracts Ci. sinensis, R. communis, N. tabacum, and Ca. annuum. The mortality of D. neivai increased in the first 72 hr in all treatments. The extracts of N. tabacum, Ca. annuum, and A. indica were more repellent to D. neivai that those of Ci. sinensis, Ar. Absinthium, and R. communis. Antifeeding effect was higher with Ci. sinensis and R. communis. The increased mortality of D. neivai by Ci. sinensis can be explained by the effect of this compound on the respiratory system of insects. Extracts of Ci. sinensis, R. communis, N. tabacum, and Ca. annuum repelled and caused mortality of D. neivai and, thus, can be used in integrate pest management programs of this pest in oil palm plantations.